Application of hot compress technique with Chinese herbal medicine package in a patient with knee osteoarthritis and related nursing management (中药热奄包技术应用于1例膝骨关节炎患者的效果观察) - LI Suqian (李苏茜); TANG Ling (唐玲); LI Ye (李野); WANG Huaxin (王华新); WANG Chun (王纯); LU Lin (芦琳); ZHAO Xueli (赵丽雪); YAO Jianshuang (姚建爽) (Journal of International Translational Medicine Limited, 2021)
This paper summarized the effect of hot compress technique with Chinese herbal medicine package in a patient with knee osteoarthritis and related nursing management. Health education, hot compress technique with Chinese herbal medicine package and continuous nursing were carried out to relieve the joint pain symptoms of the. The visual scale of Osteoarthritis Index (WOMAC scale) was used as the evaluation standard. The scores of WOMAC scale decreased, the scores of pain, stiffness and daily activity decreased, and the clinical symptoms improved after intervention. The hot compress technique with Chinese herbal medicine package is potentially effective to alleviate the joint symptoms of patients with knee osteoarthritis, delay the development of the disease and improve the quality of life. (本文回顾1例膝骨关节炎患者应用中药热奄包的治疗效果及护理经验。对患者进行健康教育, 开展中药热奄包技术和延续性护理, 采用骨性关节炎指数可视化量表(WOMAC量表)评价干预效果。干预后WOMAC量表各项评分均降低, 患者疼痛、僵硬、日常活动能力评分降低, 临床症状改善明显。中药热奄包技术能够明显缓解骨痹患者的关节症状, 延缓病情发展, 提高患者的生活质量。)